Cloning genes of p49, p72, pe199l, pe248r and cd2vinto Pichia Pastoris gs115 - Trong Binh, Nguyen; Pham, Thai Gia Hoa; Tran, Trung Hieu; Vu , Pham Thanh Phu; Nguyen, Nguyen Ly; Xuan, Phat Dinh (Vietnam Journal of Biotechnology, 2024)
African swine fever (ASF), caused by the African swine fever virus (ASFV), poses a significant threat to pig populations worldwide. ASFV is a double-stranded DNA virus. In recent years, 54 structural proteins and more than 100 proteins have been involved in viral infection found in macrophages of diseased pigs. Among these, p49 and p72 are essential capsid proteins crucial for forming the viral capsid. Additionally, pE199L and pE248R, located in the inner viral membrane, are critical for membrane fusion, a necessary step for viral entry into host cells. Another important player is CD2v, a type I transmembrane protein involved in the infection process. In this research, to develop subunit vaccines against ASFV, we focused on cloning the genes encoding these five proteins—p49, p72, pE199L, pE248R, and CD2v—into the pPIC9K plasmid for expression in the Pichia pastoris GS115 yeast strain. The viral genomic DNA was extracted from blood samples of infected pigs, and the genes encoding the five proteins were successfully amplified using Phusion PCR. The PCR products of each gene were then digested with EcoRI and NotI restriction enzymes and ligated into the pPIC9K plasmid. After that, we transformed the recombinant plasmids into Escherichia coli DH5α for amplification and purification. The plasmids were subsequently linearized with SalI and introduced into P. pastoris GS115 through electroporation. The selection of appropriate media and PCR analysis of the genomic DNA confirmed the successful generation of five recombinant P. pastoris GS115 strains. This work paves the way for the development of a recombinant protein vaccine against ASF by using the Pichia pastoris GS115 in the future.